2021
DOI: 10.1002/oby.23251
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccines are effective in people with obesity: A position statement from The Obesity Society

Abstract: The position statement is issued by The Obesity Society in response to published literature, as well as inquiries made to the Society by patients, providers, Society members, policy makers, and others regarding the efficacy of vaccines in persons with obesity against SARS‐CoV‐2, the virus that causes COVID‐19. The Obesity Society has critically evaluated data from published peer‐reviewed literature and briefing documents from Emergency Use Authorization applications submitted by Pfizer‐BioNTech, Moderna, and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 23 publications
2
32
0
3
Order By: Relevance
“…Remarkably, the available clinical evidence and a recent position statement showed that vaccines are not less effective for individuals with obesity and that they are an important protection against COVID-19 [4,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the available clinical evidence and a recent position statement showed that vaccines are not less effective for individuals with obesity and that they are an important protection against COVID-19 [4,7].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, researchers fear that vaccines against SARS-CoV-2 might not be as effective in people with obesity [5], since studies on vaccines against influenza, hepatitis B, and rabies have shown a reduced immune response in these individuals [5,6]. To date, the available clinical evidence demonstrates that the efficacy of mRNA vaccines against SARS-CoV-2 does not differ among individuals with obesity compared to those without obesity [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Another study assessing the correlation between abdominal obesity (AO) and response to mRNA vaccines reported that after two doses of BNT162b2 vaccine lower antibody peak was found among infection-naïve individuals with AO compared to individuals without AO [ 44 ]. Contradictory to these findings, some studies have also found comparable vaccine efficacies in individuals with obesity and those without [ 45 , 46 ].…”
Section: Bnt162b2 Vaccination In At-risk Individualsmentioning
confidence: 99%
“…profilaktyka powinna zaczynać się od zdrowego trybu życia. Wtedy szczepienia będą skuteczniejsze, a ryzyko wystąpienia takich chorób mniejsze [38][39][40][41].…”
Section: Skuteczność Szczepień W Warunkach Realnychunclassified